Synthesis and Characterization of Cobalt Nanoparticles Using Poly(vinyl pyrrolidone) and Sodium Dodecyl Sulphate - Al-Amin, Md.; Alam, J. (Asian Journal of Chemistry, 2015)
In this paper, cobalt nanoparticles were synthesized via wet chemical reduction method using hydrazine as reducing agent. The morphology of synthesized cobalt nanoparticles were studied with or without of poly(vinyl pyrrolidone) as well as an anionic surfactant sodium dodecyl sulphate. SEM with EDX facilities and TEM were employed to investigate the size of the nanostructures as well as the morphology of cobalt nanoparticles. The effect of poly(vinyl pyrrolidone) as well as an anionic surfactant-sodium dodecyl sulphate has been observed and found that it was potential candidate for tailoring the size of cobalt nanoparticles. Moreover, poly(vinyl pyrrolidone) were displayed a suitable coating agent for preventing agglomeration during synthesis of cobalt nanoparticles.